2021
DOI: 10.1093/pubmed/fdab213
|View full text |Cite
|
Sign up to set email alerts
|

Are schools drivers of COVID-19 infections—an analysis of outbreaks in Colorado, USA in 2020

Abstract: Background The impact of school closures/reopening on transmission of SARS-CoV-2 in the wider community remains contested. Methods Outbreak data from Colorado, USA (2020), alongside data on implemented public health measures were analyzed. Results There were three waves (n = 3169 outbreaks; 61 650 individuals). The first was led by healthcare settings, the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A recent study conducted in USA investigated differences among three waves and among different working places, finding that schools experienced 11% of identified outbreaks, yet involved just 4% of total cases, whereas adult education outbreaks (2%) accounted for disproportionately more cases (9%). The authors concluded that schools were not the key driver of the latest wave in infections [61]. Some studies found an increase in infections with opening of schools, but they are mainly modeling studies [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in USA investigated differences among three waves and among different working places, finding that schools experienced 11% of identified outbreaks, yet involved just 4% of total cases, whereas adult education outbreaks (2%) accounted for disproportionately more cases (9%). The authors concluded that schools were not the key driver of the latest wave in infections [61]. Some studies found an increase in infections with opening of schools, but they are mainly modeling studies [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…21 These findings align with studies conducted globally, whereby outbreaks in school settings documented limited transmission. Other studies have associated low transmission with the implementation of public health measures [22][23][24] ; further, when schools have reopened, they have not been associated with increases in community transmission. 25 26 Even when cases have increased in communities following school openings, it is challenging to disentangle whether increases in school outbreak incidence may have led to an increase in community incidence, as workplace mobility patterns also play a role in community incidence.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Other scientific works address multiple infection sources, such as in the workplace, leisure, educational and sanitary centers ( 29 ). For example, in Lakha et al ( 30 ), most of the identified outbreaks started in workplaces, educational centers, and healthcare facilities, whereas the number of primary infections having a social origin was small.…”
Section: Introductionmentioning
confidence: 99%